2021
DOI: 10.3390/jcm10020228
|View full text |Cite
|
Sign up to set email alerts
|

Links between Inflammation and Postoperative Cancer Recurrence

Abstract: Despite complete resection, cancer recurrence frequently occurs in clinical practice. This indicates that cancer cells had already metastasized from their organ of origin at the time of resection or had circulated throughout the body via the lymphatic and vascular systems. To obtain this potential for metastasis, cancer cells must undergo essential and intrinsic processes that are supported by the tumor microenvironment. Cancer-associated inflammation may be engaged in cancer development, progression, and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 190 publications
(70 reference statements)
0
25
0
Order By: Relevance
“…In our analysis, only 32 DE lncRNAs were shared among the three different bovine milk-originated S. aureus strains, which reminded us that when studying host–pathogen interactions, heterogeneity between strains should be considered. The chronic inflammation engaged in the progress of cancer is widely recognized [ 36 38 ], and the pathways of breast cancer and basel cell carcinoma are exclusively enriched in the comparison of CL vs. CC, which implied the potential harm of strain L (isolated from a cow with low milk SCC) to the host. Moreover, previous studies reported that the host’s inflammatory response and cytokine expression level are dependent on pathogen concentration [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our analysis, only 32 DE lncRNAs were shared among the three different bovine milk-originated S. aureus strains, which reminded us that when studying host–pathogen interactions, heterogeneity between strains should be considered. The chronic inflammation engaged in the progress of cancer is widely recognized [ 36 38 ], and the pathways of breast cancer and basel cell carcinoma are exclusively enriched in the comparison of CL vs. CC, which implied the potential harm of strain L (isolated from a cow with low milk SCC) to the host. Moreover, previous studies reported that the host’s inflammatory response and cytokine expression level are dependent on pathogen concentration [ 39 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have proposed the concept of early recurrence to characterize recurrence that occur within few months of pancreatic cancer resection; however, they did not reach an agreement on cut-off values (varying from 6 to 12 months) and ignored the certain group that might have showed relapse before the rst time of their follow-up or postoperative adjuvant therapy. The concept, hyperprogression HPD was mostly referred to in the eld of immunotherapy; however, growth-stimulating effects from surgical trauma-induced immunosuppression were also mentioned in recent studies 5,14 . The in ammatory response played a critical role in tumor invasion, progression, and metastasis by promoting tumor angiogenesis and decreasing anticancer effects 14 .…”
Section: Discussionmentioning
confidence: 99%
“…The concept, hyperprogression HPD was mostly referred to in the eld of immunotherapy; however, growth-stimulating effects from surgical trauma-induced immunosuppression were also mentioned in recent studies 5,14 . The in ammatory response played a critical role in tumor invasion, progression, and metastasis by promoting tumor angiogenesis and decreasing anticancer effects 14 . According to previous studies, systemic response to tissue damages led to surgeries and the subsequent wound healing triggered a cascade alteration in cellular immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Inflammation triggers inflammatory diseases including pulmonary diseases, Alzheimer's disease and diabetes, cancer, atopic dermatitis, arthritis, asthma, gout, psoriasis, anemia, Parkinson's disease, multiple sclerosis, and depression (Bruno et al 2020;Ahmad et al 2021;Carranza-Naval et al 2021;Choi et al 2021;Kinoshita and Goto 2021;Romano et al 2021). These diseases have become increasingly threatening to human health (Wu et al 2020;Placha and Jampilek 2021).…”
Section: Introductionmentioning
confidence: 99%